Demonstration of gamma-ray pipe-monitoring capabilities for real-time process monitoring safeguards applications in reprocessing facilities. Issue 7 (3rd July 2018) - Rodriguez, Douglas Chase; Tanigawa, Masafumi; Nishimura, Kazuaki; Mukai, Yasunobu; Nakamura, Hironobu; Kurita, Tsutomu; Takamine, Jun; Suzuki, Satoshi; Sekine, Megumi; Rossi, Fabiana; Koizumi, Mitsuo; Seya, Michio; et al.
ABSTRACT: Nuclear material in reprocessing facilities is safeguarded by random sample verification with additional process monitoring applied to solution masses and volumes within the tanks to maintain continuity-of-knowledge of the operational processes. Measuring the unique gamma rays of each solution as the material flows through pipes connecting all tanks and process apparatuses could potentially improve process monitoring by verifying the composition in real time. We tested this gamma-ray pipe-monitoring method using plutonium-nitrate solution transferred between tanks at the Plutonium Conversion Development Facility at the Tokai Reprocessing Plant of the Japan Atomic Energy Agency. The gamma rays were measured with a lanthanum-bromide detector and a list-mode data acquisition system to obtain both time and energy information to evaluate the solution nuclear material as well as process conditions. Developed offline, we demonstrate this method can determine isotopic composition, flow-rate, volume, and process timing of a solution batch, introducing a viable online, in-line, unattended capability for improved process monitoring safeguards verification. The process and measurement details are presented here along with a description of the analyses used and the results of the evaluation.